THE EFFECT OF PRODUCT QUALITY AND BRAND IMAGE ON PURCHASE DECISIONS AT WARUNG MIE SUREEE CEK PON RANGKAYA INTERSECTION - Nuratul Ikramah; Cut Sukmawati; Maisyura; Teuku Zulkarnaen; Sufi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This article examines the influence of product quality and brand image on purchasing decisions at Warung Mie Suree Cek Pon Simpang Rangkaya. The main question to be answered in this study is whether product quality and brand image are factors that influence customer satisfaction that occurs at Warung Mie Suree Cek Pon Simpang Rangkaya. During the observation, the researcher saw that respondents stated that they decided to make a purchase at Warung Mie Suree Cek Pon Simpang Rangkaya because of the quality of the product provided. This assessment is based on personal experience and reputation from other people or the media. From the results of the pre-research survey obtained, the average respondent answered that they decided to make a purchase at Warung Mie Suree Cek Pon Simpang Rangkaya because the brand image information they got was appropriate. This type of research is quantitative using a survey method and data collection techniques, namely a questionnaire in the form of a print out given to customers of Warung Mie Suree Cek Pon Simpang Rangkaya with a total of 96 respondents. The data analysis method used is the instrument test and the classical assumption test and uses multiple linear regression tests with the help of SPSS software version 25 to help researchers calculate the data that has been obtained. The results of this study can be concluded that based on the partial test (t), the product quality variable does not have a positive and insignificant effect on purchasing decisions. While the brand image variable has a positive and significant effect on purchasing decisions. Then based on the simultaneous test (F), the product quality and brand image variables simultaneously or together have an effect on purchasing decisions